Perception of CPR quality: Influence of CPR feedback, Just-in-Time CPR training and provider role. (February 2015) - Cheng, Adam; Overly, Frank; Kessler, David; Nadkarni, Vinay M.; Lin, Yiqun; Doan, Quynh; Duff, Jonathan P.; Tofil, Nancy M.; Bhanji, Farhan; Adler, Mark; Charnovich, Alex; Hunt, Elizabeth A.; et al.
Abstract: Aim: Many healthcare providers rely on visual perception to guide cardiopulmonary resuscitation (CPR), but little is known about the accuracy of provider perceptions of CPR quality. We aimed to describe the difference between perceived versus measured CPR quality, and to determine the impact of provider role, real-time visual CPR feedback and Just-in-Time (JIT) CPR training on provider perceptions. Methods: We conducted secondary analyses of data collected from a prospective, multicenter, randomized trial of 324 healthcare providers who participated in a simulated cardiac arrest scenario between July 2012 and April 2014. Participants were randomized to one of four permutations of: JIT CPR training and real-time visual CPR feedback. We calculated the difference between perceived and measured quality of CPR and reported the proportion of subjects accurately estimating the quality of CPR within each study arm. Results: Participants overestimated achieving adequate chest compression depth (mean difference range: 16.1–60.6%) and rate (range: 0.2–51%), and underestimated chest compression fraction (0.2–2.9%) across all arms. Compared to no intervention, the use of real-time feedback and JIT CPR training (alone or in combination) improved perception of depth ( p < 0.001). Accurate estimation of CPR quality was poor for chest compression depth (0–13%), rate (5–46%) and chest compression fraction (60–63%). Perception of depth is more accurate in CPR providers versus team leaders (27.8% vs. 7.4%; p = 0.043) when using real-time feedback. Conclusion: Healthcare providers' visual perception of CPR quality is poor. Perceptions of CPR depth are improved by using real-time visual feedback and with prior JIT CPR training.